Web application performance analysis based on component load testing / Nor Hafiza Abd Samad - Abd Samad, Nor Hafiza (2014)
Performance of many Web sites depends on the load on the site at peak time under varying conditions. Performance testing is normally conducted in a reasonably simulated environment with the help of performance testing tools. However, performance of a Web site depends on various parameters and each parameter must be tested under varying stress levels. It is not possible to draw a common denominator for performance parameters to test the Web site due to complexity of Web sites. Different parts of the Web site must be tested with different parameters under varying condition and stress level. The objectives of this study are to determine how many user simultaneously work with the web server without a perceptible slowdown, to evaluate the server response time taken by a web server to serve client and compare the result with the existing web stress tool and verify the performance of above results by measuring the response time for web application and increase an Eduzone web application performance using caching technique. In this work, three test beds has been constructed focusing on various factors that influence the web application performance, and present an Eduzone Web Application that we develop in order to measure the performance of web application. To optimize the web application performance, we apply the concept of cacheable and no cacheable web application. The results presented in this study show that placing some intermediate caches in the network can significantly improve the performance of those applications that distribute content using the only support of client’s caches, reducing the bandwidth usage in the network and the response time to the clients.